Agro-morphological characterization of soybean germplasm: AGRO-MORPHOLOGICAL CHARACTERIZATION OF SOYBEAN GERMPLASM - PREETI PAINKRA; RAJEEV SHRIVASTAVA; D SUNIL K NAG (Journal of Oilseeds Research, 2019)
Two hundred seventy three germplasm lines of soybean including three checks (JS-97-52, Bragg and JS-335) were evaluated for agro-morphological charactersin an augmented block design at Raipur, Chhattisgarh. These traits belonged to two categories viz., qualitative-measured through visual observation like anthocyanin pigmentation (present and absent), flower colour, pod colour, leaf colour, etc and quantitative- measurable traits like plant height, size ofseed (100-seeds weight g), etc. The entire (273 genotypes) soybean under study showed wide range of genetic variation in respect to these traits. The frequency distributions of 20 agro-morphological characters showed variable range of characters. Most of the genotypes were distinguishable on the basis of characters published in the DUS guidelines.